(untitled) (ASEAN Engineering Journal, 2012)
This paper presents an experimental study on the flexural strength of CFRP box beams with two laminate structures: a cross-ply (CP) and a quasi-isotropic (QI). Three specimens were prepared for each laminate structure. The specimens were tested under four point bending, and the material tests of each laminate structure were conducted. The bending tests showed that QI exhibited higher flexural strength than CP and that they had different failure configurations. Also, flexural strength is calculated based on beam theory with Tsai-Wu criterion or maximum stress criterion to be compared with the experimental one. Moreover, in order to discuss a buckling behavior, buckling stress is calculated. It is shown that the calculated flexural strength based on Tsai-Wu criterion agrees well with the experimental one and that the buckling stress exhibits higher value than compressive stress at the flexural strength in the bending test.